Analisis Kesenjangan terhadap Peran Kebijakan Publik dalam Mendorong Inklusi Keuangan Masyarakat Marginal - Nabila Haninda Mufidah; Tjitjik Rahaju (Jurnal Administrasi dan Kebijakan Publik, 2026)
Financial inclusion is a crucial instrument for creating equitable economic growth, particularly for marginalized communities who face limited access to formal financial services. However, a gap remains between the inclusive objectives of public policy and the reality of its implementation on the ground. This study aims to analyze the gap in the role of public policy in promoting financial inclusion for marginalized communities through a qualitative descriptive approach using a literature study method. Data were collected from various literature sources such as scientific journals, policy reports, government regulations, and financial institution documents. The analysis reveals inconsistencies in policy implementation, limited synergy between policy actors, and suboptimal local needs-based interventions. This study concludes that public policy needs to be directed towards a more participatory and contextual approach to address the structural challenges in expanding financial inclusion for marginalized communities.